The province within the metropole: The history of Soviet architecture as seen from mid-century Leningrad - V. G. Bass (Шаги, 2025)
The article is based on archival materials dealing with the discussions of the manuscript of “Concise Course of the History of Soviet Architecture” at the Leningrad branch of the Academy of Architecture of the USSR. The course was the first comprehensive work on the history of Soviet architecture prepared at the turn of the 1940s–1950s by the staff of the Academy and published in mass circulation only in the post-Stalin period. The materials demonstrate a degree of diversity of opinions unexpected in the epoch of political and ideological dictatorship. Along with the “Moscow” (or “Central”) viewpoint, there were also some “local” ones characteristic of local architectural communities, even within the Soviet metropole. In particular, there was the Leningrad school of architecture and architectural history with its characteristic values, priorities, and hierarchies (related to both historic and contemporary construction). The peculiar “local view” on the history from the city’s architecture during the three Soviet decades can be seen in architects’ attempts to establish the professional succession from the pre-Revolutionary architecture and to claim the succession of the classical tradition, in their unexpectedly loyal evaluation of Leningrad Constructivist architecture, in their constant stressing the ensemble qualities of the architecture of Saint Petersburg — Leningrad, in the choice of buildings and personalities for the “Concise Course”.